Produção de alimentos, educação do campo, educação em ciências : interações problematizadas em abordagem freireana - Rodrigues, Marcos Antonio Oliveira (2020)
This study problematizes educational processes in Science Education in the context of Rural Education. The research aimed to interpret an educational process that starts from thematic investigation and problematizing dialogues, having interactions between Science Education and Rural Education due to Freirean problematizations. In this context, the study site was a municipal school located in the central region of the state of Rondônia, which serves students from the Palmares settlement. In this qualitative study, there were stages of planning and development of thematic research, the organization of the research scenario, the collection of information from the students involved in the educational process. The thematic investigation had as a problematic theme the “food production”, which was carried out with students of the 8th year of Elementary School. This stage of the research sought to characterize the study scenario, identify the subjects and problematize the theme that guides the research. Questionnaires, interviews and sentence complementation were used with the research instrument. After the construction of the data, they were systematized and analyzed based on the theoretical framework that supports this study. The students participating in the research are all residents of the settlement, with a total of 17, ranging in age from 12 to 17 years old, attending the 8th grade of elementary school. They live an average distance of 6.8 km from the school. In addition to working from home, they seek another source of income, outside of their property. Therefore, here it presents a reality of students with an average age of 14 years old who are already committed to their work. Most have always lived in the countryside. In addition, 5 interviews were conducted on food production and on the main foods they consume daily. It is noticed that students consume practically the same types of food: rice, beans, meat, potatoes, pasta, bananas, squash and salad, apple, carrot, cassava and tomato are added to this list. It was identified as common or the consumption that it produces in the community itself, such as potatoes and meat. However, there is consumption of compound foods in urban products. The data indicate that none of the students interviewed knows the origin of the foods that are composed of these activities. From another question, we perceive a relationship with different chemical inputs when they argue that these foods are not spoiled, because pesticides and preservatives are used in their production. In one example, the student denounces and revolts against this technique and is responsible for climate change. Thus, it was possible to identify dialogues about local problems that can affect Education in Science and Education in the Field, which require to be implemented as a right of the people in the field to restrict their permanence in the field. The results and discussions of this research are promoted through interpretations of the constructed data, data that present the possibilities and potential of Science Education for the formation of the most critical citizen.